Community Acquired, Nursing Home Acquired and Hospital Acquired Pneumonia: A Five-Year Review of the Clinical, Bacteriological and Radiological Characteristics - CW Chow; LR Lee-Pack; N Senathiragah; M Rawji; M Chan; CK Chan (Canadian Journal of Infectious Diseases)
Purpose: To assess the contemporary clinical, bacteriological and radiographic features of hospitalized patients with community acquired (ca), nursing home acquired (na) and hospital acquired pneumonia (ha) and to examine patient outcome.